UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI BUMI DAN BENDA LANGIT DENGAN MODELROLE PLAYING PADA SISWA KELAS VI SDN 1 SUKARAME - Pebrinda, Pebrinda (Lentera: Jurnal Ilmiah Kependidikan, 2019)
Efforts to improve student understanding require effective and efficient methods. In addition, appropriate learning media are also needed so that students can master the competencies expected. In the teaching and learning process, the media has a very important role in supporting the achievement of learning objectives. The application of the demonstration method by using visual playing role playing in learning about the earth and celestial bodies is expected to arouse students' curiosity and interest as well as motivation to learn, also can facilitate students in understanding the material and information conveyed. While the objectives of this study are to increase understanding of the earth and celestial bodies in 6th grade students through the application of demonstration methods by using visual media to play roles. This research uses action research as much as three rounds. Each round consists of four stages: design, activity and observation, reflection, and refinement. The targets of this study were students of grade VI SDN 01 Sukarame, Bandar Lampung City. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of analysts it was found that student achievement increased from cycle I to cycle II namely, cycle I (25.92%), cycle II (92.59%). The conclusion of this research is the teaching method of demonstration with role playing visual media can positively influence learning motivation of Grade VI students of SDN 01 Sukarame,Bandar Lampung City, and this learning model can be used as an alternative to learning science.